PLCs in Action: Innovative Teaching for Struggling Grade 3-5 Readers. - D'Ardenne, Charna; Barnes, Debra G.; Hightower, Elaine S.; Lamason, Pamela R.; Mason, Mary; Patterson, Paula C.; Stephens, Nancy; Wilson, Carolyn E.; Smith, Vickie H.; Erickson, Karen A. (Reading Teacher, 2013)
A group of elementary school reading teachers used their time in a Professional Learning Community to develop a systematic intervention to address the needs of struggling readers in grades 3 to 5. Working as a team, they identified a collection of books that was culturally diverse, high interest, appealing to boys and girls, aligned with curriculum across the grades, and equally representative of fiction and non-fiction. Using the collection of books as a starting place, the group wrote lessons that addressed decoding, vocabulary development, comprehension strategies, and responding to standardized test question stems. The resulting intervention led to growth in reading level as well as accelerated progress on the state mandated end of grade test in reading. The PLC offered this group of experienced reading teachers a district-supported framework for working together to create a locally relevant solution for the students they teach.